Integration Factors Influencing Halal’s Cosmetics Purchase Intention on Non-Muslim Women in Indonesia - Basalamah, Jafar; Basalamah, Fahdina Hadi (BISNIS, 2024)
This research examines the cosmetics purchase intention of non-Muslim women by analyzing islamic advertising, islamic branding, purchase intention, and consumer’s satisfaction.  Data were collected from 168 Indonesian Non-Muslim women in four cities through online questionnaire using the purposive sampling technique, with Smart PLS used for analysis. The findings showed that Islamic Branding significantly influences customers purchase intention and satisfaction among non-muslim women in using halal cosmetics. This research was carried out to explore and examine the purchase intention of non-Muslim women in using halal and to capture a significant segment of the company products in order to obtain a competitive edge worldwide.